The Role of Bhabinkamtibmas in Preventing the Crime of Theft of Two-Wheeled Motorized Vehicles in the Banda Aceh Police Legal Territory - Doholy Musra Perdana (Advances in Police Science Research Journal, 2022)
This research was motivated by the increasing number of motor vehicle theft crimes in the Banda Aceh Police jurisdiction. The high level of community activity in Bnada Aceh City has made the criminal acts that occurred become high as well. And the pattern of prevention that is prioritized by the Police is more acceptable to the public than the pattern of repression or repression.Writing this thesis uses a qualitative approach with descriptive research type. Data collection techniques by interview, observation, and review of documents. There are primary and secondary data sources and the theories used to analyze are role theory, routine activity theory, technical competency theory and work efficiency theory.The results of the study found that the role of Bhabinkamtibmas in preventing criminal acts of theft of motorized vehicles, especially two-wheelers, was conducting sambaing, counseling the community, and implementing the door to door system. There are factors that influence Bhabinkamtibmas in carrying out its duties, namely supporting factors consisting of directing the implementation of tasks, productivity. , motivation, evaluation and work environment then the inhibiting factors consist of time, supervision, completeness aspects and level of education. Based on the discussion of the research, the writer gives suggestions to the leadership to conduct analysis and evaluation to Bhabinkamtibmas personnel and has standardization for the assessment of Bhabinkamtibmas members, emphasizes providing material to the public regarding the theft of two-wheeled motorized vehicles, improving suggestions and infrastructure owned, and providing rewards. and punishment for members of Bhabinkamtibmas as motivation to work.